Identification of Gifted Students in Oman: Gender and Grade Differences on the Gifted Rating Scales–School Form. (September 2017) - Hassan Hemdan Mohamed, Ahmed; Mahdi Kazem, Ali; Pfeiffer, Steven; Alzubaidi, Abdul-Qawi; Abu Elwan, Reda; Ambosaidi, Abdullah; Al-Washahi, Mariam; Al-Kharosi, Tarek
Research suggests that teacher-completed gifted screening scales can reduce undernomination of students with culturally and linguistically diverse backgrounds. The purpose of this study was to examine the use of the Gifted Rating Scales–School Form (GRS-S) in the identification of gifted students in Oman. The participants of the study represented a national sample of 907 students from Grades 1 to 10 in five governorates in Oman. The MANOVA showed that the main effect of the gender was statistically significant on the GRS subscales. Females' mean scores on four subscales (Intellectual Ability, Academic Achievement, Artistic Talent, and Motivation) were higher than males'. A statistically significant effect of the grade was found on the GRS subscales. Third-grade students' ratings of artistic ability were higher than other students' grades.